2010
DOI: 10.1093/jxb/erq027
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium reduces sugar uptake in tobacco cell cultures: a potential cause of inhibited elongation but not of toxicity

Abstract: Aluminium is well known to inhibit plant elongation, but the role in this inhibition played by water relations remains unclear. To investigate this, tobacco (Nicotiana tabacum L.) suspension-cultured cells (line SL) was used, treating them with aluminium (50 μM) in a medium containing calcium, sucrose, and MES (pH 5.0). Over an 18 h treatment period, aluminium inhibited the increase in fresh weight almost completely and decreased cellular osmolality and internal soluble sugar content substantially; however, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…High Al concentrations decrease the uptake of nutrients, such as Mg, Ca, P, K, Zn and Fe [13]. The inhibition effect of Al on elongation and cell death might involve two phases; the early phase is distinguished by low sugar uptake and inhibition elongation, and the later phase is involved in ROS generation, eventually leading to cell death [4]. ROS production, respiration inhibition and ATP depletion are important events of Al toxicity in plant cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…High Al concentrations decrease the uptake of nutrients, such as Mg, Ca, P, K, Zn and Fe [13]. The inhibition effect of Al on elongation and cell death might involve two phases; the early phase is distinguished by low sugar uptake and inhibition elongation, and the later phase is involved in ROS generation, eventually leading to cell death [4]. ROS production, respiration inhibition and ATP depletion are important events of Al toxicity in plant cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…During an 18-h Al treatment of tobacco cells in a simple medium containing calcium and sucrose, the cell fresh weight, soluble sugar content and osmolality decreased concomitantly over the first 6 h (earlyphase symptoms) and then remained constant, in contrast to their continual increases in the untreated culture. The production of ROS and callose was observed after 6 h of Al exposure (late-phase symptoms) (Yamamoto et al 2002(Yamamoto et al , 2003Abdel-Basset et al 2010). Thus, we proposed the biphasic Al action and that the inhibition of sucrose uptake by Al could be a primary event to decrease osmolarity, whereby Al represses water uptake and cell elongation.…”
Section: Introductionmentioning
confidence: 87%
“…In previous studies, we used suspension-cultured tobacco cell lines (SL, BY-2) to elucidate the mechanism of Al cytotoxicity. Cells in the logarithmic growth phase showed symptoms similar to those of roots, such as inhibited cell elongation and cell death (physiological responses) as well as production of reactive oxygen species (ROS) and callose (biochemical responses) (Yamamoto et al 2002(Yamamoto et al , 2003Abdel-Basset et al 2010). In those studies, cell death was evaluated by several biological markers such as respiration inhibition, loss of plasma membrane integrity (monitored by staining with Evans blue or fluorescein diacetate; FDA), and growth arrest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of NPs have been used in a number of ways to reduce disease levels and prevent the development and spread of pathogens, thus preserving yield and quality crop products. Abdelbasset et al [8] reported that both chitin and chitosan nanoparticles have demonstrated antiviral, antibacterial, and antifungal properties, and have been explored for many agricultural uses.…”
Section: Introductionmentioning
confidence: 99%